GPR171 Agonist Reduces Chronic Neuropathic and Inflammatory Pain in Male, But Not Female Mice - Ram, Akila; Edwards, Taylor; McCarty, Ashley; Afrose, Leela; McDermott, Max V.; Bobeck, Erin N. (Frontiers in Pain Research, 2021)
Chronic pain is a growing public health crisis that requires exigent and efficacious therapeutics. GPR171 is a promising therapeutic target that is widely expressed through the brain, including within the descending pain modulatory regions. Here, we explore the therapeutic potential of the GPR171 agonist, MS15203, in its ability to alleviate chronic pain in male and female mice using a once-daily systemic dose (10mg/kg, i.p.) of MS15203 over the course of 5 days. We found that in our models of Complete Freund’s Adjuvant (CFA)-induced inflammatory pain and chemotherapy-induced peripheral neuropathy (CIPN), MS15203 did not alleviate thermal hypersensitivity and allodynia, respectively, in female mice. On the other hand, MS15203 treatment decreased the duration of thermal hypersensitivity in CFA-treated male mice following 3 days of once-daily administration. MS15203 treatment also produced an improvement in allodynia in male mice, but not female mice, in neuropathic pain after 5 days of treatment. Gene expression of GPR171 and that of its endogenous ligand BigLEN, encoded by the gene PCSK1N, were unaltered within the periaqueductal gray in both male and female mice following inflammatory and neuropathic pain. However, following neuropathic pain in male mice, the protein levels of GPR171 were decreased in the periaqueductal gray. Treatment with MS15203 then rescued the protein levels of GPR171 in the periaqueductal gray of these mice. Taken together, our results identify GPR171 as a GPCR that displays sexual dimorphism in alleviation of chronic pain. Further, our results suggest that GPR171 and MS15203 have demonstrable therapeutic potential in the treatment of chronic pain.